The CLC-5 2Cl−/H+ exchange transporter in endosomal function and Dent's disease - Lippiat, Jonathan; Smith, Andrew (Frontiers in Physiology, 2012)
CLC-5 plays a critical role in the process of endocytosis in the proximal tubule of the kidney and mutations that alter protein function are the cause of Dent’s I disease. In this X-linked disorder impaired reabsorption results in the wasting of calcium and low molecular weight protein to the urine, kidney stones, and progressive renal failure. Several different ion-transporting and protein clustering roles have been proposed as the physiological function of CLC-5 in endosomal membranes. At the time of its discovery, nearly twenty years ago, it was understandably assumed to be a chloride channel similar to known members of the CLC family, such as CLC-1, suggesting that chloride transport by CLC-5 was critical for endosomal function. Since then CLC-5 was found instead to be a 2Cl-/H+ exchange transporter with voltage-dependent activity. Recent studies have determined that it is this coupled exchange of protons for chloride, and not just chloride transport, which is critical for endosomal and kidney function. This review discusses the recent ideas that describe how CLC-5 might function in endosomal membranes, the aspects that we still do not understand, and where controversies remain.